Managing conflict escalation in forestry: logging versus local community interests in Baru Pelepat village, Sumatra, Indonesia - Yasmi, Yurdi; Schanz, H. (2010)
Two extremes of forest conflict exist: low- and high-intensity conflicts. Theoretical debate on how forest conflict escalates from one extreme to the other has begun to take place; however, empirical research is lacking. Our paper aims to explore the conflict escalation process using a case study approach. We explored whether two theoretical building blocks of conflict escalation (stages and patterns) can be evaluated at the field level.We conducted fieldwork in Baru Pelepat village, Sumatra, to investigate a conflict between a logging company and a local community.We performed interviews and focus group discussions with key stakeholders. The conflict revolved around an unclear boundary between a state forest, within which the logging company operated, and the communal forest, which led to local community opposition to logging activity. The conflict escalated over time as parties failed to find a solution.We describe escalation stages associated with the conflict and also the pattern of conflict escalation. The findings suggest that theoretical frameworks of conflict escalation are applicable at field level. A number of practical options for managing the conflict and the implications for wider forest management are discussed. While understanding the conflict escalation process does not necessarily guarantee effective settlement of a conflict, it nonetheless helps to strategically devise conflict management efforts.